Prey Abundance And Population Dynamics Of South American Fur Seals (Arctocephalus Australis) In Peru - Cardenas Alayza, Susana (2012)
South American fur seals (Arctocephalus australis) continue to survive in Peru in spite of commercial harvesting, periodic disappearance of prey (i.e., El Niño), and competition with the Peruvian anchoveta fishery. I investigated the ability of the Peruvian population of fur seals to recover from catastrophic declines at two temporal and spatial scales. The first analysis determined intrinsic rate of growth (r) and the potential carrying capacity (K*—the number of fur seals that could be supported in Peru in the absence of sealing and El Niño) from 1880–2010, and the second used pup counts from 1984–2010 to determine the relationship between prey abundance and the timing of pupping at an important fur seal breeding site in southern Peru. Model results indicated that South American fur seals in Peru have an intrinsic growth rate r of 0.20 and a potential carrying capacity K* of 115,000 seals. Recent counts (2007) show that current population is at 33% of the estimated mean numbers of fur seals alive from 1880-1925. Analysis of 25 years of counts of pups and adult females at the breeding site showed a correlation between anchoveta biomass and mean birth dates (r2 = 0.59, P<0.01) and with the ratio of pups to females (r2 = 0.66, P<0.01) in the upcoming breeding seasons. It also revealed a 2-week shift in the mean birth date that may reflect a change in the age structure of the population. Numbers of pups born tended to be lower in years with low anchoveta biomass, as did recruitment of young females. Monitoring daily numbers of pups born and adult females appears to be a useful means to assess the feeding conditions encountered by South American fur seals in Peru. My study also suggests that South American fur seals are adapted to survive in extremely disturbed environments and have the potential to rapidly recover following population declines. Whether or not they ever again achieve their potential carrying capacity will depend upon protection of breeding rookeries, a continued harvest ban, reduced bycatch, incidental captures and illegal poaching, regulation of anchoveta fishing quotas and good environmental conditions.